The Influence of Internal and External Factors on Financial Performance in Enhancing the Competitiveness of Small and Medium Enterprises in Papua - Mugiati, Mugiati; Wadjo, Muhammad Amin; Aditama, Muhammad Irfan (Journal of International Conference Proceedings, 2023)
This study aims to identify and analyze the direct influence of internal factors, which consist of Human Resource Management, Production, Marketing, Working Capital, and Organizational aspects, as well as external factors, including Government Policies and Financial Performance, on Small and Medium Enterprises' competitiveness in Papua. Data was collected through observations, interviews, and questionnaires. The data was analyzed using Structural Equation Modeling (SEM) with Amos Software. The analysis results indicate that human resource management does not significantly affect the financial performance of Small and Medium Enterprises in Papua, whereas production, marketing, working capital, and organizational factors do influence financial performance. The analysis also shows that these internal factors impact the competitiveness of Small and Medium Enterprises in Papua. Furthermore, external factors, such as government policies and competition, affect both the financial performance and competitiveness of small and medium enterprises in Papua. Additionally, financial performance is found to be linked to the competitiveness of Small and Medium Enterprises in Papua.